The great themes of Scriptures - Rohr, Richard; Martos, Joseph (Pasay City : Saint Paul Publications, 1989)
Contents.--v.1. Old Testament.--v.2. New Testament.
Keywords: Bible -- Study and teaching -- Catholic Church